Muslims in the Military: A Cause or a Solution for Issues of National Security - Luke Wessell (Australian Journal of Islamic Studies, 2017)
Australian Muslims rarely join the Australian Defence Force. There is no evidence this statistic is changing, no sign it is likely to change in the near future, and meanwhile the Australian Muslim population continues to grow faster than the general Australian population. If statistical trends continue, at best the situation will become far more noticeable, and at worst it will become an issue of national security and societal cohesion. This paper discusses the risks of long-term segregation of Australian Muslims from the nation’s defence forces, and considers them alongside the risks of acting to deliberately increase in numbers of Muslims serving in the ADF. Muslim jurists face a dilemma, where the scholar who is against Islamic service in the ADF risks being perceived as not supportive of Australia’s efforts to fight ISIS, et al, and the scholar who comes out in support of ADF service risks being perceived by their own community as endorsing Western imperialism and the collateral damage suffered by innocent Muslims in the same geographical areas. Similar dilemmas for ADF leadership also exist and are the cause of apparent contradictions between public statements and grassroots reality.